O ensino de Filosofia como responsabilidade pelo mundo: uma abordagem a partir de Hannah Arendt - Oliveira, Elineide Alves de (2022)
The dissertation entitled "The teaching of Philosophy as responsibility for the world: an approach from Hannah Arendt" proposes itself as a true "invitation to think" aimed at the teaching of Philosophy, and brings a didactic approach to high school, from of the philosophical categories presented by the German thinker, related to education and the understanding of the world as an approach strategy to be used by educators. The proposal is not indicated as a path to be followed or an infallible recipe, but above all as a strategy through which it is possible to aim for advances in the level of student involvement in relation to the reflections that are proposed to them. Therefore, the reflection initially addresses the concept of crisis presented by the author and continues with the exposition of the categories of world, responsibility and belonging. The didactic proposal presented at the end serves as an approach strategy to introduce the figure of the German thinker Hannah Arendt to the knowledge of students and follows the format of a didactic unit structured from three sequences entitled Knowing Hannah Arendt through biography, Knowing Hannah Arendt through through the trailer and Getting to know Hannah Arendt through the interview. The intention is to favor reflective dialogue and problematize the meaning of occupation and human activity in the world through classes that contribute to the emergence of an awareness of self and favor the creation of bonds between students and Philosophy and, from there, with the world. . The conclusion allows us to understand education as a philosophy teaching and evidences its formative function constituted by stimuli to the action of a reflective thinking. A thinking that, if preliminarily occurs in the scope of individuality, in the scope of the particular through exercises of thought, when externalized in the ambience of a classroom, these thoughts expand and become public in a true 'action between men'. Notably, it is at this moment that the sense of plurality, care and preservation of the world becomes evident, conditions that are so dear to Hannah Arendt.